Medico-legal death investigations and autopsies in Istanbul, Turkey - (:unkn) unknown (Churchill Livingstone, 1998)
There are two different organizations in forensic medicine in Turkey: the universities and the Council of Forensic Medicine (CFM). The CFM is an official body of the Ministry of Justice and serves as an expert witness on technical and medical subjects. The basic duty of the universities is education in the medical schools with the cooperation of the CFM. This study examines 3064 medico-legal death investigations and 2548 autopsies performed in the CFM, Ministry of Justice, Istanbul and in the eleven units of CFM in Istanbul during 1996. The age and sex distributions, the incidence and causes of deaths were reviewed.